2021
DOI: 10.1002/cjoc.202100508
|View full text |Cite
|
Sign up to set email alerts
|

Tunable System for Electrochemical Reduction of Ketones and Phthalimides

Abstract: Main observation and conclusion Herein, we report an efficient, tunable system for electrochemical reduction of ketones and phthalimides at room temperature without the need for stoichiometric external reductants. By utilizing NaN3 as the electrolyte and graphite felt as both the cathode and the anode, we were able to selectively reduce the carbonyl groups of the substrates to alcohols, pinacols, or methylene groups by judiciously choosing the solvent and an acidic additive. The reaction conditions were compat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 65 publications
0
39
0
2
Order By: Relevance
“…Sodium azide, used as a supporting electrolyte, was shown to have a positive effect on the oxidation of formic acid, as the electron transfer was enforced. When acetic acid was used instead of formic acid, diphenylmethanol was found as the main product from the hydrogenation of benzophenone [110] …”
Section: Anodic Counter Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium azide, used as a supporting electrolyte, was shown to have a positive effect on the oxidation of formic acid, as the electron transfer was enforced. When acetic acid was used instead of formic acid, diphenylmethanol was found as the main product from the hydrogenation of benzophenone [110] …”
Section: Anodic Counter Reactionsmentioning
confidence: 99%
“…When acetic acid was used instead of formic acid, diphenylmethanol was found as the main product from the hydrogenation of benzophenone. [110] Another non-green but practical laboratory solution is the oxidation of sterically hindered amines. Xiang and coworkers reported the reduction of cyclic imides to hydroxylactams (Scheme 21).…”
Section: Anodic Additivesmentioning
confidence: 99%
“…Bei Verwendung von Essigsäure anstelle von Ameisensäure wird Diphenylmethanol aus der Hydrierung von Benzophenon als Hauptprodukt beobachtet. [110] Eine weitere nicht nachhaltige, aber praktische Laborlösung ist die Oxidation von sterisch gehinderten Aminen. es ist sehr sauer und bildet nach dem Protonenaustausch mit dem Lösungsmittel neutrale Radikale.…”
Section: Anodische Additiveunclassified
“…Es hat sich gezeigt, dass Natriumazid als Leitsalz einen positiven Effekt auf die Oxidation von Formiat hat, da der Elektronentransfer bevorzugt wird. Bei Verwendung von Essigsäure anstelle von Ameisensäure wird Diphenylmethanol aus der Hydrierung von Benzophenon als Hauptprodukt beobachtet [110] …”
Section: Anodische Gegenreaktionenunclassified
“…Thus, the development of a sacrificial anode-free process such as paired electrolysis would be highly desirable [40][41][42][43][44]. The group of Wang recently reported the sacrificial anode-free electroreduction of benzophenone derivatives to afford vic-1,2-diols using over-stoichiometric NaN 3 under acidic conditions, but appropriate precau-tions should be taken for in situ-generated explosive and toxic HN 3 [45]. Kim et al reported the formation of vic-1,2-diols in the sacrificial anode-free electrocarboxylation of 1-phenylethanol and benzyl alcohol which involves tetramethylpiperidine-1-oxyl-mediated alcohol oxidation as an anodic event [46].…”
Section: Introductionmentioning
confidence: 99%